Asymptomatic Cardiac Toxicity in Long-Term Cancer Survivors: Defining the Population and Recommendations for Surveillance - Carver, Joseph R. (2013)
Advances in the treatment of pediatric and adult cancer have reduced the mortality rates from these disorders and have led to an ever-increasing population of long-term survivors. Chemotherapy and radiotherapy may cause premature cardiac disease that may be asymptomatic or symptomatic. All patients exposed to chemotherapy with cardiotoxic potential or chest radiotherapy have stage A heart failure and the goal of surveillance and treatment is to prevent progression to stages B-D. Screening strategies, including the use of biomarkers, echocardiography, and expert opinion surveillance and treatment recommendations, are presented.